Pengaruh Pola MACD Histogram IHSG Terhadap Pola MACD Histogram Perusahaan Dari Daftar Indeks LQ45 (Periode Februari s.d Juli 2015) Bursa Efek Jakarta [Effect of MACD Histogram IHSG Patterns to Patterns of Companies Listed on the Jakarta Stock Exchange LQ-45 (Period February till July 2015)] - Heri Fatkhurrokhim; Didi Sundiman (Universitas Pelita Harapan, 2015)
The purpose of this study is to determine the effect of MACDIHSG pattern to the MACD Company pattern in the L045 index on the period of February until July 2015 at the Indonesia Stock Exchange. This study also aims to facilitate investors to make investment decisions in the stock market. This study provides benefits to capital market investors, especially for stock investors in the Indonesia Stock Exchange as a mean of enhancing their insights in the development of technical analysis on investing. For the general public as well in order to know that investing in the stock market differs from gambling since there are analyzes that easy and can be applied very simply. In addition, this research aims to enhance the reader's desire to invest in the stock market. The samples were the closing data price of IHSG and shares ofLQ45 in the period of February until July 2015 in the Indonesia Stock Exchange. Based on the hypothesis testing, it can be explained that the MACD Histogram IHSG has a significant effect on 38 issuers listed in LQ45. As for the difference between the MACD Histogram effect against one company with another company that is very small. From the 38 stocks that rank on the top 3 company, the Summarecon Agung Tbk is on the top 1, that amounted to 98.3348%, then Alam Sutera Reality Lestari Tbk amounted to 98.2376%, and Adhi Katya (Persero) Tbk amounted to 98.1320%. The third of these shares have MACD Histogram movement that approaching the MACD Histogram IHSG.